POLA ASUH ORANG TUA DALAM INTERNALISASI PENDIDIKAN KARAKTER RELIGIUS PADA REMAJA USIA 12-15 TAHUN DI DUSUN SURABAYA DESA SINGARAYA KECAMATAN SEMPARUK TAHUN 2023 - Sarkawati Sarkawati; Suriadi Suriadi; Asyruni Multahada (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This undergraduate thesis discusses parenting styles in the internalization of religious character education among adolescents aged 12-15 years in Dusun Surabaya, Singaraya Village, Semparuk Subdistrict. This research has three objectives: 1) to describe parenting styles in the internalization of religious character education among adolescents aged 12-15 years in Dusun Surabaya, Singaraya Village, Semparuk Subdistrict in 2023; 2) parental efforts in the internalization of religious character education among adolescents aged 12-15 years in Dusun Surabaya, Singaraya Village, Semparuk Subdistrict in 2023; and 3) the supporting and inhibiting factors of parenting styles in the internalization of religious character education among adolescents aged 12-15 years in Dusun Surabaya, Singaraya Village, Semparuk Subdistrict in 2023. This research employs a qualitative approach with a phenomenological research type. Data collection techniques included interviews, observation, and documentation. Data analysis techniques used were reduction analysis, data display, verification, and conclusion drawing. The data validity checking techniques employed were source and technique triangulation, as well as member checking. The results of this research indicate that: 1) Parenting styles in the internalization of religious character education among adolescents aged 12-15 years in Dusun Surabaya, Singaraya Village, Semparuk Subdistrict in 2023 utilize permissive and democratic parenting styles. 2) Parental efforts in the internalization of religious character education among adolescents aged 12-15 years in Dusun Surabaya, Singaraya Village, Semparuk Subdistrict in 2023 are carried out through dialogue, stories, role modeling, habituation, advice, parables, and rewards. 3) Supporting and inhibiting factors of parenting styles in the internalization of religious character education among adolescents aged 12-15 years in Dusun Surabaya, Singaraya Village, Semparuk Subdistrict in 2023 include: The supporting factor is the parents’ religion or belief in shaping children’s behavior in accordance with religious character values. The inhibiting factors include a lack of parental supervision when children are not at home, education, socio-economic status, environmental factors, and a lack of guidance for children.